Perfil alcaloídico de Açucena (Hippeastrum elegans) e efeito anti-inflamatório em neutrófilo e micróglia - Souza, Ana Sheila de Queiroz (2021)
Hippeastrum elegans is a bulbous Amaryllidaceae, native to Brazil, which produces alkaloids with anti-inflammatory potential, including lycorine and galanthamine. Inflammation, although it is a defense mechanism of the organism against harmful stimuli; when triggered inappropriately, it is associated with the pathophysiology of many diseases of high socioeconomic impact, such as neurodegenerative diseases, cancer, and, recently, the condition of Covid-19. In this sense, the objective of this work was to determine the alkaloid profile of H. elegans cultivated bulbs and to investigate the anti-inflammatory effect of alkaloid fractions in two cell models (human neutrophil and murine microglia). Therefore, the alkaloid fractions were extracted by liquid-liquid partition of bulbs grown for 15 months and harvested in six harvest times (5, 7, 9, 11, 13 and 15 months/FHE05 - FHE15). Then, they were analyzed by gas chromatography-mass spectrometry (GC-MS) and, after spectral deconvolution, trends in chemical composition were determined by Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA). Ahead, the chemically distinct fractions were investigated for toxicity and anti-inflammatory activity in human neutrophil (cell degranulation model) and microglia, line BV-2 (nitric oxide production - NO). In addition, anti-inflammatory alkaloids in human neutrophils were broken down by Partial Least Squares (PLS) regression analysis. In this way, 41 compounds were detected, common to the six harvest times of H. elegans. PCA and HCA, in a complementary way, pointed out the separation of the samples in three distinct groups (I: FHE05, FHE07 and FHE09; II: FHE11 and III: FHE13 and FHE15). The three representative fractions/group (I: FHE07; II: FHE11 and III: FHE15) investigated, FHE07 showed the best effect on neutrophil degranulation measured by the release of myeloperoxidase and the production of reactive oxygen species, based on the chemiluminescence, after induction with PMA (phorbol-myristate-acetate), not associated with toxicity (MTT test and LDH activity). PLS indicated lycorine and a derivative, 11,12-dehydro2-methoxy-assoanine, as the compounds responsible for the anti-inflammatory activity of the FHE07 fraction. While FHE15 (2.5 µg/mL) significantly reduced the production of NO in microglia (line BV-2) in non-toxic concentrations (MTT test and flow cytometry). Therefore, H. elegans undergoes variations in the alkaloids profile according to the time of cultivation and the fractions, FHE07 and FHE15, demonstrate a promising anti-inflammatory effect, in human neutrophil and murine microglia (line BV-2), respectively, which justify additional research